Immune Activation and CD127 Expression on T Lymphocyte Subsets of a Chinese Cohort of Pediatric AIDS Patients with Different Viral Responses - Jin, Changzhong; Zhang, Fujie; Wu, Lijuan; Xie, Tiansheng; Cheng, Yuewu; Tang, Zhirong; Wu, Nanping (Current HIV Research, 2012)
Immune activation and IL-7/IL7 receptor (CD127) systems are significant for CD4+ T cell defect in AIDS patients. However, the association between immune activation and CD127 expression on T lymphocyte subsets in Chinese pediatric AIDS patients is not well studied. Here, we recruited a cohort of 194 Chinese pediatric AIDS patients: 135 good viral responders (GVRs) and 59 poor viral responders (PVRs). CD38high and HLA-DR+CD8+ T lymphocytes and CD127 expression on T-cell subsets were determined by flow cytometry. Viral load was detected using a quantitative RT-PCR assay. The results showed that pediatric AIDS patients had a lower memory CD4+ percentage and a higher memory CD8+ T-cell percentage. The percentage of naive CD4+T-cells was higher, especially in GVRs. The percentage of CD38high and HLA-DR+CD8+ in PVRs was higher than in GVRs and controls, being positively correlated with viral load and memory CD8+, but negatively correlated with memory CD4+ T cells. The percentage of CD127+ memory CD4+ T cells in GVRs was higher than in PVRs, but lower than in controls. CD127 expression was positively correlated with percentage of CD4+ subsets and naive CD8+ T cells, but negatively correlated with percentage of memory CD8+ T cells. Our study demonstrates that the percentages of CD38high and HLA-DR+ CD8+ T cells are good markers to evaluate immune activation of pediatric AIDS patients, and elevated immune activation has a more profound effect on memory T cells. IL- 7/CD127 system is more important to maintain the proportion of naive T cells.
Keywords: CD127